Metoda punktu siodłowego aproksymacji rozkładów - Nikodem, Anna (Saddlepoint method for probability distribution approximation, 2007)
When the exact distribution cannot be conveniently obtained, we can use an approximation. In the paper the saddlepoint approximation is described. This method is used for approximating density of the aggregated amount of claims, where the individual claim amounts generated from the insurance portfolio are independently and identically distributed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 195-201